ANALISA RISIKO TAHAP PERAWATAN JALAN DALAM PENERAPAN PERFORMANCE BASED CONTRACT PADA PROYEK JALAN DI JAWA TIMUR - Prihartanto, Eko (Universitas Nahdlatul Ulama Sidoarjo, 2016)
Road as the main infrastructure in cross overland to connect starting area to the destination area. The level of damage that occurred after the implementation reduce the road’s service quality. Performance Based Contract (PBC) has stages such as Design, Build, Operation, and Maintenance. PBC is expected to minimize the budget for road construction due to damage that routinely occurs every year. PBC has the maintenance stage to meet the performance who have risk reducing road maintenance after road completion and operation. Risk variables in this study use variables in the maintenance stage from the PBC application in Eastern Java road project. It uses Probability Impact Analysis method to analyze road maintenance risk in PBC application. The results are highest score of risk variable in the maintenance stage as the descriptive analysis references to compare the threat and opportunity in PBC application. Then, it is used to create strategy in order to fulfil dominant risk in the maintenance stage.